Sosialisasi Pentingnya Studi Lanjut ke Perguruan Tinggi bagi Santri Pondok Pesantren di Era 4.0 - Abdullah, Ahmad Anis; Mubarok, Muhammad Najib; Adawiya, Robiatul; Sholihah, Dyahsih Alin; Richardo, Rino; Zahro, Siti; Rahcman, Alfan Alfian (Universitas Islam Negeri Raden Intan Lampung, 2022)
The era of the industrial revolution 4.0 demands an increase in the quality of human resources to be able to compete globally, for that further study at university is one of the efforts to improve the quality of human resources. One of the communities that has great potential but has not been touched by the socialization of the importance of further study to universities in the industrial revolution 4.0 era is Islamic boarding schools. This community service program in the form of socialization is carried out on the basis of collaboration between Alma Ata University Yogyakarta and Islamic Boarding Schools in the Special Region of Yogyakarta (DIY) to provide socialization to students about the importance of further study to higher education in the 4.0 era. The method used is counseling or direct socialization to students. The purpose of this service is to increase the awareness and motivation of students in Islamic boarding schools on the importance of further study in higher education in the industrial revolution 4.0 era. The data collection technique was carried out after the socialization was carried out in the form of a questionnaire of interest. The results obtained showed that after the socialization, 81% of the participants were motivated to continue their further studies at universities in the industrial revolution 4.0 era.